THE IMPACT OF HUMAN DEVELOPMENT INDEX (HDI), ELECTRICITY AND SANITATION INFRASTRUCTURE AVAILABILITY ON INCOME INEQUALITY IN SUMATERA ISLAND - Fathur Rahman; Weri; Cut Zakia Rizki; Cut Risya Varlitya; Talbani Farlian (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This research aims to analyze the relationship between the Human Development Index (HDI), the availability of electricity and sanitation infrastructure on income inequality in the island of Sumatera. This research uses panel data from 10 provinces on the island of Sumatra in the 2011-2022 period. This research method used panel data regression analysis using the Random Effect Model (REM). Based on the results of research that has been conducted, it shows that HDI does not have a significant influence on income inequality, the availability of electricity infrastructure has a significant negative influence on income inequality, and sanitation has a significant negative influence on income inequality. The results of this study is expected to serve as a reference for the government in formulating policies aimed at reducing income inequality and improve equitable development on Sumatra Island.